Does Newborn Care, Feeding Practices and Immunization Status Have an Effect on Anthropometric Measurements of Infants? - Mishra, Mili; Dwivedi, Shraddha; Hassan, M A; Parveen, Khurshid; Khan, M A (National Journal of Community Medicine, 2015)
Introduction: Immediate proper care of newborn is vitally important for survival, growth and development of a baby. In the home, a number of simple strategies have been shown to prevent infant and childhood illness and malnutrition, including breastfeeding, appropriate complementary feeding practices and seeking a complete course of vaccines for infants in their first year of life. The present study has been undertaken to assess the effect of newborn care, infant feeding practices and immunization status on nutritional status of infants in Jasra Block of Allahabad district. Method: A cohort study conducted in a community among newborns born during the period of November 2011 to April 2012. IEC (Information, Education and Counselling) was given to their mothers from last three months of pregnancy till the newborns completed one year of age. The effect of newborn care, infant feeding practices and immunization status was assessed in terms of anthropometric measurements. Results: More than half of the infants i.e. 47 (60.26 %) gained weight to reach within the normal range and weight of 33 (42.31%) infants was below 2 standard deviation. Conclusion: Newborn care, infant feeding practices, immunization status and lesser episodes of illnesses have a positive effect on nutritional status of infants in terms of weight and length.